Strategi Guru Membangun Kesadaran Moral Siswa Terhadap Pentingnya Norma Kesusilaan di SMP Negeri 1 Sukoharjo - Adhillah, Aisyah Niya (Academy of Education Journal, 2024)
Teacher strategy is a way for teachers to overcome and break the chain of bullying in the school environment of SMP Negeri 1 Sukoharjo. This study discusses the problems in the school environment and the teacher's strategy in building students' moral awareness of the importance of moral norms. This approach uses qualitative with descriptive research. This data source was obtained from 11 informants and documentation. This data collection was carried out by means of observation, interviews and documentation. The results showed that the violation of moral norms in the school environment of SMP Negeri 1 Sukoharjo as follows: Bullying, dating in the school environment, not helping friends when they fall on the floor. so that teachers create a strategy to form students understand the norms of decency and the formation of student character in accordance with applicable laws such as the following: approach, embedding norms of decency in phase D elements of the 1945 Constitution of the Republic of Indonesia, implementation of the Pancasila Student Profile and finally the enforcement of school regulations.